(untitled) (Global Journal of Human-Social Science, 2023)
Under the conditions of the decentralization reform the system of budget equalization in Ukraine underwent significant changes which took place in the direction of transition from vertical equalization of expenditures to horizontal equalization of incomes Today a mixed system of budget equalization is being formed in Ukraine in which emphasis is placed on the horizontal equalization of incomes with the use of separate tools for the vertical equalization of expenditures The main problems of budget equalization in Ukraine are the insufficient volume of own revenues in local budgets the high level of dependence of local budgets on transfers from the State budget the insufficient validity of the procedure for calculating the tax capacity index the low level of financial autonomy of communities the lack of a clear division of powers between state authorities and bodieslocal self-government transfer of powers to the level of local self-government without appropriate financial support significant differentiation of regions according to the level of socio-economic development The problem of restoring the district level of local self-government is in a frozen state